The Influence of Celebrity Endorsers on Purchase Intention of Instagram Social Media Users - Okta Gabriel Mamahit; David P. E. Saerang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2022)
This study aims to determine the effect of attractiveness,Â trustworthiness, andÂ expertise possessed by celebrity endorsers on the purchase intention of Instagram social media users partially and simultaneously, data were collected through a questionnaire method with a population of 400 and by using the slovin formula, 80 samples were obtained. Based on the results of the analysis found that the three Attractiveness, trustworthiness, and expertise factors have a positive and significant influence on the purchase intention of Instagram social media users.